Back Cover: Ultrafast Magic‐Angle Spinning: Benefits for the Acquisition of Ultrawide‐Line NMR Spectra of Heavy Spin‐1/2 Nuclei (ChemPhysChem 6/2016). Issue 6 (11th February 2016) - Pöppler, Ann‐Christin; Demers, Jean‐Philippe; Malon, Michal; Singh, Amit Pratap; Roesky, Herbert W.; Nishiyama, Yusuke; Lange, Adam
Abstract : Ultrafast magic‐angle spinning has several advantages for the study of heavy spin‐1/2 nuclei: rapid and easy measurement, requires only a small amount of material, and gives a high accuracy description of the local electronic environment. More information can be found in the Communication by J.‐P. Demers, Y. Nishiyama, A. Lange et al. onpage 812 in Issue 6, 2016 (DOI:10.1002/cphc.201501136 ).